Profile of Nosocomial Sepsis in a Neonatal Intensive Care Unit of Tertiary Care Hospital in Eastern Part of Nepal - Yadav, Sunil Kumar; Niroula, Niraj; Giri, Arun (Journal of Nepal Paediatric Society, 2021)
Introduction: Nosocomial sepsis constitutes a global health problem. They lead to significant morbidity and mortality in both developed and resource-limited countries. The objective of the study was to describe the profile of nosocomial sepsis in neonatal intensive care unit (NICU). Methods: This was a prospective descriptive study conducted in a teaching and referral NICU. All neonates in NICU who did not have any sign of infection at admission and remained hospitalized for at least 48 hours were observed. Profile of nosocomial infection was analyzed with descriptive statistics. P value of < 0.05 was considered significant wherever applicable. Results: The incidence rate and density of nosocomial sepsis were 47.3% and 39.3 infections per 1000 patient-days respectively. Blood stream infection was the commonest nosocomial infection. Pseudomonas aeruginosa was the most commonly isolated agent in blood cultures of patients with nosocomial sepsis. Conclusions: This study revealed a high incidence of nosocomial sepsis. Hence, there is urgent need to adopt policies to prevent these infections.